2005
DOI: 10.1007/s11172-006-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photochromic properties of a single-crystalline spiro[indolinepyranopyridinium] salt

Abstract: The molecular and crystal structure of single crystalline 5´ hydroxymethyl 1,3,3,7´,8´ pentamethylspiro[indoline 2,2´ [2H ] pyrano[3,4 b]pyridinium] iodide (1) was studied. The crystal structure is composed of cation layers separated by iodide ions and provides a sufficient volume for the phototransformation of compound 1. The spectroscopic and photochromic properties of this compound in the crystalline state were investigated. Upon irradiation with light at 270-370 nm, up to 600 layers of single crystals are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Such a structure should prevent the isomerization of MC forms of the molecules and formation of closed SP forms in crystals, as observed for spiropyrans in the non salt form, 7 unlike the salt forms. 5, 6 Spectral and photochemical properties. It has been shown that compound 1 synthesized previously 2 exhibits photochromic properties in solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a structure should prevent the isomerization of MC forms of the molecules and formation of closed SP forms in crystals, as observed for spiropyrans in the non salt form, 7 unlike the salt forms. 5, 6 Spectral and photochemical properties. It has been shown that compound 1 synthesized previously 2 exhibits photochromic properties in solutions.…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been shown 3,4 that the structure of the magnetic anionic sublattice of bimetallic oxalates [M III M II (ох) 3 ] -allows cation size variation to perform in a wide range, and the crystal structure of the spiropyran cation in salts with chloride and iodide anions is found to be favorable for reversible photochromic transformations of spiropyrans. 5, 6 These features of the structures of the cationic and anionic sublattices allowed crystal chemical modeling of photochromic ferromagnets to be per formed. 1,2 In this case, it was important that the SP + cation was involved in the reaction in the closed form.…”
mentioning
confidence: 99%
“…As a rule, spiropyrans and spirooxazines are not photochemically active in microcrystalline pow ders and single crystals. 9 This is explained by the fact that the phototransformations caused by bond cleavage between the spiro carbon atom and oxygen atom followed by isomerization of the molecule require large free volume.…”
Section: Methodsmentioning
confidence: 99%
“…Salts of spiropyrans (SP + X -) and spirooxazines (SO + X -) hold promise for the development of hybrid polyfunctional materials, combining photochromic and magnetic properties in a single crystal lattice [6][7][8][9]16], in which the spiropyran or spirooxazine cations have photochromic properties. Thus, the synthesis, structure, and photochemical properties of cationic spiropyrans and spirooxazines have recently attracted considerable investigation [8,9,[14][15][16][17]. A completely new class of hybrid polyfunctional compounds has recently been discovered.…”
mentioning
confidence: 99%